The reality of development of academic programs at King Khalid University and The Requirements and Obstacles to Development according to the philosophy of interdisciplinary studies from the point of view of faculty members - Elshrbeni, Ghada Hamza Mohamed (Journal of Educational and Psychological Sciences, 2022)
The research aimed to study the reality of the development of academic programs at King Khalid University and the requirements and obstacles to development according to the philosophy of interdisciplinary studies from the point of view of faculty members. The descriptive approach was used and a questionnaire of (40) sentences, which was applied to a sample of (102) faculty members at King Khalid University. The results related to the opinions of faculty members about the reality of developing study programs at King Khalid University in light of the philosophy of interdisciplinary studies showed that: the practices related to this axis came with a medium degree by (4,08), and the opinions of the members of the study sample about the obstacles to the development of interdisciplinary programs came with a medium degree (3.38) which is a high percentage, and the most important requirements for developing study programs at King Khalid University are came with a medium degree (3.24). , the presence of statistically significant differences in the axis of the reality of development, and that; Depending on the variables; Gender in favor of females, and according to the degree variable, there are no statistically significant differences, and according to the specialization variable, there are statistically significant differences, counting the level of significance (0.05) between the health specialization and the theoretical specialization in favor of the theoretical specialization.. And there is a statistically significant difference, counting the level of significance (0.05) between the specialization. Theoretical and practical specialization in favor of the theoretical specialization, and with regard to (obstacles) there is a statistically significant difference at the level of significance (0.05) between the degrees of assistant professor, associate professor and professor in favor of associate professor. There is no statistically significant difference at the level of significance (0.05) between the health specialization and the theoretical specialization. And between health specialization and practical specialization. And there is a statistically significant difference at the level of significance (0.05) between the theoretical specialization and the practical specialization in favor of the practical one. A suggested proposal for the development of the study programs at King Khalid University has been developed in light of the interdisciplinary philosophy.